Development of Somatosensory Perception in Children: A Longitudinal QST-Study - Hirschfeld, Gerrit; Zernikow, Boris; Kraemer, Nicole; Hechler, Tanja; Aksu, Fuat; Krumova, Elena; Maier, Christoph; Magerl, Walter; Blankenburg, Markus (Neuropediatrics, 2012)
Cross-sectional studies on somatosensory perception in children demonstrate lower pain thresholds for children compared with adolescents. The aim of the present longitudinal study was to replicate these age-related differences in a longitudinal design. Total 38 children and adolescents aged 6 to 16 years (two girls and two boys within each year) participated in this study. Quantitative sensory testing (QST) according to the protocol of the German research network on neuropathic pain (DFNS) was assessed twice with an interval of 15.8 ± 3.0 months. Bland–Altman analyses describe the short-term reliability of the measurements. Intraindividual sensory development was measured using paired t-test and quantified by effect sizes Cohen's d between the two measurements. QST parameters showed good short-term reliability. Over a period of 1 year, children became less sensitive to painful stimuli, especially to cold pain, pressure pain, and mechanical pain. No systematic developmental changes were observed in response to the other somatosensory stimuli. QST is reliable over short retest intervals. In line with previous results from cross-sectional studies, we find a decrease in pain sensitivity with increasing age but no differences in nonnociceptive somatosensory processing over a period of 1 year in children between 6 and 16 years of age. Taken together, these results highlight the importance of a reference-based interpretation of the individual QST data.
Keywords: somatosensory perception; children; development; quantitative sensory testing; longitudinal assessment